Impact of the SARS-COV-2 pandemic on access to health services in Angola: a focus on diagnosis and treatment services for tuberculosis - Caminada, Susanna; Benoni, Roberto; Dente, Maria Grazia; Robbiati, Claudia; Tomas, Joaquim; Natali, Giulia; De Simeis, Luca; Da Silvia, Nsuka; Lazary, Neusa; Tienabe, Paulo Siene; Putoto, Giovanni; Costanzo, Marianna; et al. (Frontiers in Public Health, 2025)
IntroductionThe SARS-CoV-2 pandemic had a profound impact on healthcare systems worldwide. In sub-Saharan Africa, it significantly affected several health services for infectious diseases such as HIV; however, less is known about its impact on Tuberculosis (TB). This study aimed to assess the pandemic’s impact on access to health services in Angola, focusing on diagnosis and treatment services for TB.MethodsAn observational study combining data from routine statistics and surveys based on ad-hoc questionnaires was conducted on TB and non-TB services between 2018 and 2022. On routine data, temporal trends were analyzed comparing different non TB- and TB-specific indicators across the five-year period using the chi-square test. Questionnaires were administered to healthcare professionals from TB/non-TB services and structured interviews were conducted with TB patients to understand their perceptions about the impact of COVID-19 pandemic.ResultsThere was a significant decline in access to TB services during the pandemic, with a substantial decrease in reported cases (−15.5% in 2020; −18.3% in 2021) and treatment rate (from 86% in 2019 to 68% in 2020), an increase in multidrug-resistant-TB (from 0.2% in 2018 to 2.1% in 2022) and TB/HIV co-infections (from 6% in 2018 to 8.8% in 2021). The impact was most pronounced in the province of Luanda (capital city). TB services in Angola were disproportionately affected compared to general healthcare access indicators. The healthcare professionals’ and patients’ questionnaires showed that fear of COVID-19, unavailability of drugs, reduced income, and transportation challenges were the main barriers to healthcare access.ConclusionThe COVID-19 pandemic negatively impacted the TB services provision in Angola. This highlights the urgent need for health systems to develop robust contingency plans to ensure the continuity of TB services during and after public health crises and to maintain essential healthcare services by supporting the healthcare workforce and addressing barriers to patient access.